Effect of Workload and Pedalling Rate on Physiological Response for Male Worker - Prithviraj Patil; A. K. Mehta; Shiwani Dhumal; Sukanya Palve; Omkar Mane; Tejaswini Patil (Archives of Current Research International, 2025)
Until about two and half centuries ago, muscle power was the prime source of energy for performing all the physical activities on our earth, and much of this power had been from human muscles. Because of the socio-economic conditions of farmers in developing countries including India, human muscle power is going to contribute energy requirements for performing many farm activities for the next two decades. Pedalling is the most efficient way of utilising power from human muscles. Pedal power enables a person to drive devices at the same or higher rate as that achieved by hand cranking, but with far less effort and fatigue. However, the use of pedal power for occupational work such as stationary farm operations has got scant attention in the past. Keeping these points into consideration a study was planned for Effect of workload and pedalling rate on physiological response for male worker. Physiological responses of 20 male subjects were studied on a computerised bicycle ergometer at four levels of power output (60, 70, 80, 90 W) four levels of pedalling rates (40, 50, 60, 70 rev/min). Analysis of data indicated that physiological responses were significantly affected with power output as well as pedalling rate. Increases in physiological responses (heart rate and oxygen consumption rate) over rest were significantly higher when pedalling frequency was 50rev/min and above 60rev/min. There was no significant difference between physiological responses at 50 and 60 rev/min. Physiological responses increased linearly with power output and were significantly different at different power outputs. The average value of physiological responses at 60W power output at male agriculture worker at 50rev/min pedalling rate were within acceptable limits for continuous pedalling work.